Isu HAM dalam Penegakan Hukum di Indonesia: Analisis Kasus Penanganan Tindak Pidana Terorisme Berdasarkan Hukum Nasional dan Internasional : (Studi Kasus Bom Bali I dan II) - Keysha Alea Azzahra; Sarah Zahira; Reita Ananta; Muhammad Arief Nurrachman; Dwiki Darmawan; M Athaullah Abhinaya (Referendum : Jurnal Hukum Perdata dan Pidana, 2024)
The Bali Bombings I on October 12, 2002, and Bali Bombings II on October 1, 2005, were major terrorist attacks that shook Indonesia and the international community. This study aims to analyze the chronology of these events, the national and international legal perspectives on handling terrorism cases, and the efforts of the Indonesian government in law enforcement. Through a national and international legal approach, this research identifies the challenges faced in enforcing the law against terrorism suspects, especially concerning the application of human rights principles. The findings indicate that while significant law enforcement efforts have been made, legal application still needs to be aligned with international legal developments and respect for human rights.